STRATEGI PENGEMBANGAN AGRIBISNIS JAMBU AIR MADU DELI HIJAU (Syzygium aqueum) di CV.WOLFFIA AGRO INDONESIA, KABUPATEN BOYOLALI - Febyani, Prisca Chrisma; Simamora, Liska (Universitas Galuh, 2023)
CV.Wolffia Agro Indonesia is an agriculture business with the commodity of green deli honey guava fruit. Guava fruit has a fairly wide market potential and high selling value because it does not have a business development strategy. The purpose of the study is to analyze alternative formulations and determine the priority strategies that companies should choose for their business development. The determination of participants by purposive sampling of 5 people with IFE, EFE, and SWOT Matrix analysis method. The results from the study are there are 2 factors that affect the company consisting of internal factors and external factors. Internal factors have 5 indicators of strengths and 6 weaknesses, while external factors have 5 indicators of opportunities and 4 threats. The data that has been processed produces a value of X: 1.46 and Y: 1.99, entered into Quadrant I which means aggressive. The conclusion of this research is that there are 12 alternative strategies and 4 priority alternative strategies that can be implemented by CV Wolffia Agro Indonesia. The priority strategies that can be carried out are increasing guava fruit agribusiness by utilizing human resources and agricultural technology, utilizing the land area for better guava fruit growth, optimizing guava fruit production to meet market demand, and establishing cooperation with residents.